Studi Keefektifan Program Kemitraan Orang Tua di Lembaga PAUD Kabupaten Wonosobo - Farida, Nur; Mulyani, Pamungkas (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2023)
The growth and development of early childhood is a shared responsibility between parents and PAUD institutions, for this reason the importance of the partnership program between parents and PAUD institutions is an effort to accelerate the formation of children's character. The purpose of this research is to determine the effectiveness of the parent partnership program that has been implemented in the PAUD institution in Wonosobo district. The research was carried out using the survey method in collecting data through observation sheets and unstructured interviews which were used to strengthen information obtained from information sources, the samples used in this study were 9 (nine) PAUD institutions with information subjects being teachers & school principals, Guardians & Students in each sample. The results of this study are that parent-parent partnership activities have been carried out but there are deficiencies that disrupt the process, most of which come from parents of students, so that there is a need for support from all parties, both from parents, PAUD institutions, the government, the Ministry of Education and related offices, Village/Kelurahan Government officials, as well as Workplace Agencies to be able to support the program.